Efficient Bayesian nonparametric hazard regression - Matthias Kaeding (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
We model the log-cumulative baseline hazard for the Cox model via Bayesian, monotonic P-splines. This approach permits fast computation, accounting for arbitrary censorship and the inclusion of nonparametric effects. We leverage the computational efficiency to simplify effect interpretation for metric and non-metric variables by combining the restricted mean survival time approach with partial dependence plots. This allows effect interpretation in terms of survival times. Monte Carlo simulations indicate that the proposed methods work well. We illustrate our approach using a large data set of real estate data advertisements. – – Dieser Beitrag modelliert die log-kumulative Baseline-Hazard des Coxschen Regressionsmodells mittels Bayesianischer, monotoner P-splines. Der Ansatz ermöglicht schnelle Rechenoperationen, die Berücksichtigung von beliebigen Zensierungsmechanismen und die Einbeziehung von nicht-parametrischen Effekten. Durch die Kombination des Restricted Mean Survival Time Ansatzes mit Partial Dependence Plots wird die Interpretation von metrischen und nicht-metrischen Variablen vereinfacht. Dabei wird die Recheneffizienz der Methoden ausgenutzt. So können Effekte direkt in Bezug auf Überlebenszeiten interpretiert werden. Monte Carlo Simulationen zeigen, dass die vorgeschlagenen Methoden gut funktionieren. Der Ansatz wird mittels eines großen Datensatzes, bestehend aus Immobilienanzeigen, illustriert.
Keywords: C11; C14; C41; 330; Bayesian survival analysis; nonparametric modeling; penalized spline: restricted mean survival time